The effect of the electronic structure and flexibility of the counteranions on magnetization relaxation in [Dy(L)2(H2O)5]3+ (L = phosphine oxide derivative) pentagonal bipyramidal SIMs. Issue 3 (9th December 2019) - Díaz-Ortega, Ismael F.; Herrera, Juan Manuel; Dey, Sourav; Nojiri, Hiroyuki; Rajaraman, Gopalan; Colacio, Enrique
Abstract : The effects of the electronic structure and flexibility of triflate anions in a new high- U eff TBPY-7 SMM, [Dy(OPCy3 )2 (H2 O)5 ](CF3 SO3 )3 ·2OPCy3, have been analyzed. Abstract : We report here a new Dy III -SIM [Dy(OPCy3 )2 (H2 O)5 ](CF3 SO3 )3 ·2OPCy3 (OPCy3 = tricyclohexylphosphine oxide) with a pentagonal bipyramidal geometry, which exhibits a blocking temperature T B = 8.5 K and an anisotropy barrier U eff = 562 K. Ab initio calculations show that this complex exhibits the largest U calc = 732 K among the Dy III -SIM complexes containing the [Dy(L)2 (H2 O)5 ] 3+ (L = phosphine oxide derivative) cationic unit, which is essentially due to the electronic effects of the triflate anion that increase the charge difference between the oxygen atoms of the ligands L coordinated in axial positions and those belonging to the equatorial water molecules. This charge difference enhancement, which is also reflected in a larger difference between the corresponding Dy–O distances ( Δ ), appears to be the driving force to increase the U calc value. The comparatively smaller experimental U eff value observed for this compound has been justified by the flexibility of the structural network due to the size of the triflate counteranions. The absence of a clear correlation between T B and U eff (or U calc ) suggests the involvement of Raman and QTM mechanisms in the magnetization relaxation process.